THE ISSUE OF TRANSFER PRICING AND MULTINATIONAL ENTERPRISES IN INDONESIA: A NOTE TO TAX TRIBUNAL DECISION - DAHLAN, MUHAMMAD (Jurnal BPPK: Badan Pendidikan dan Pelatihan Keuangan, 2024)
The growing trend of cross-border transactions conducted by multinational enterprises sheds new light on the consequences of transfer prices between affiliates among multinationals. This study aims to explore the battle between multinationals and the Indonesian tax authority, Directorate General of Taxes, concerning tax consequences of intra-group service arrangements as stipulated in three tax cases brought to the Indonesian tax court in 2021 and 2022. This study finds uses legal doctrine analysis as the methodology and finds that when scrutinizing the intra-group service transactions among members of multinationals, there was a lack of understanding from the Indonesian tax authority officers in applying the international transfer pricing guidelines and domestic tax regulations. From the tax judges’ perspectives, there was an inconsistency in applying tax regulations, mainly dealing with the administrative burden of proof to benefit intra-group service treaty provisions. This study contributes to the literature by establishing certainty that there is ambiguity in the provisions of the Indonesian tax legislation, which led to different interpretations from the tax officers, multinationals, and tax court judges